Impact evaluation of a Critical Pathway for patients with Clostridium difficile infection: A pre-post analysis in a Third Level Referral Center. (March 2019) - de Belvis, Antonio Giulio; Barbara, Andrea; Giubbini, Gabriele; Traglia, Serena; Angioletti, Carmen; Ianiro, Gianluca; Masucci, Luca; Sanguinetti, Maurizio; Laurenti, Patrizia; Cambieri, Andrea; Gasbarrini, Antonio; Ricciardi, Walter; et al.
Highlights: We evaluated in a pre-post study the impact of a Critical Pathway focused on patients with Clostridium Difficile Infection in an Italian Teaching Hospital. An overall improvement in volume, process and outcome indicators was registered. The implementation of a Critical Pathway successfully influenced appropriateness in hospital quality of care. Abstract: Background: Clostridium Difficile Infections (CDIs) have been increasing both in incidence and in severity, representing a big public health concern. Aim: The aim of this study was to evaluate the impact of a recently implemented Critical Pathway (CP) focused on patients with CDI in an Italian Teaching Hospital. Methods: The CP implementation consisted of intervention aimed to faster diagnosis and appropriateness in admission and discharge point of care; activation of a multidisciplinary team; staff training; information to patients and caregivers. In a pre-post retrospective observational study, volume, process and outcome indicators were analyzed. Findings: A total of 228 patients (128 in 2013 and 100 in 2016) were included. A decrease in the absolute number of access to the Emergency Department (p = 0.02) and an increase in hospitalization in more appropriate ward (ie gastroenterology ward, p < 0.001) were found. The median hospital length of stay decreased from 20.5 (12.5–31) days in 2013 to 16.5 (7–31) days in 2016 (p = 0.05). With regards to outcome indicators, an increase of discharge to home and a decrease of discharge to long term facilities were showed (p = 0.01 both). Despite a reduction, no statically significant differences in mortality between 2013 and 2016 were revealed by the analysis. Conclusion: In conclusion, we found quality improvement in patient hospital management. Our experience confirms that the implementation of the CP increases the appropriateness in hospital quality of care.